To elucidate the neuroprotective effect of omega-3 fatty acid supplementation in acute spinal cord injury subjects: A prospective longitudinal cohort study - Khurshid Alam Ansari; Priyank Pratap; Zeenat Ara; Muhammad Shahid Raza; Sharad Verma; Shah Waliullah; Mohd Yoosuf (Asian Journal of Medical Sciences, 2025)
Background: Spinal cord injury (SCI) is an extremely debilitating disorder. Efforts in augmenting neurological recovery and quality of life (QoL) spinal cord independence measure (SCIM) following SCI are being studied the world over. Omega 3 fatty acid is important polyunsaturated fatty acids with some roles in normal cellular metabolism they have Anti-inflammatory and antioxidant properties have a neuroprotective effect and have a role in axon regeneration. Aims and Objectives: The purpose of this study was to assess the effect of omega-3 fatty acid supplements on the recovery of neurological function in SCI patients. Materials and Methods: In our prospective longitudinal cohort study, we enrolled 26 SCI subjects and followed for 6 months, cases were selected according to selection criteria given by the American Spinal Injury Association (ASIA) Scale guidelines. Each of the enrolled study subjects was exposed to detailed personal history that was recorded in pre-designed pro forma, subjects were divided into two groups, i.e., Group 1 comprising subjects who were on conventional treatment, Group 2 comprising subjects who were on omega-3 fatty acid supplementation (465 mg docosahexaenoic acid+75 mg eicosapentaenoic acid) daily. Clinical assessment of ASIA scores and ASIA impairment scale and QoL (SCIM) was done at the time of admission and at all visits. The analytical tool used to assess the omega-3 fatty acid level through serum sample is Elisa. Data were analyzed by SPSS version 26 SPSS Inc Chicago IL USA. Result: In our study, the omega-3 fatty acid-supplemented group showed gradual increasing trends in subsequent follow-ups, and the difference was statistically significant (P<0.0001*), whereas receiver-operating characteristic analysis of omega-3 levels between cases (at different follow-ups) and controls, a significant cutoff value of 3.90 with a sensitivity of 92.31% and specificity of 84.62% was observed. Similarly, in comparison to Group I, omega-supplemented group had improved QoL as SCIM scores raised through time in Group II in comparison to Group I. Conclusion: Omega-3 fatty acid, a neutraceutical, helps in facilitating neurological and functional recovery in acute SCI in comparison to subjects on conventional treatment.